2023
DOI: 10.1159/000532059
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Bilirubin Elimination with the Cytokine Adsorber CytoSorb® and Mortality in Critically Ill Patients with Hyperbilirubinemia

Caroline Gräfe,
Michael Paal,
Martin Winkels
et al.

Abstract: Introduction: Hyperbilirubinemia is often the first evidence for any kind of liver disorder and over one-third of all patients in intensive care units (ICU) show elevated bilirubin concentrations. In critically ill patients, high concentrations of serum bilirubin are correlated with a poor outcome. Therapies to lower bilirubin concentrations are often just symptomatically and their effect on the patients’ outcome is hardly evaluated. Therefore, this study investigates whether the extracorporeal elimination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Currently, CytoSorb ® (CytoSorbents Europe GmbH, Berlin, Germany), HA 330 (Jafron Biomedical Co., Ltd., Zhuhai, China), and Toraymyxin™ (Toray Medical Co., Ltd., Tokyo, Japan) are three mainstream hemoadsorbers that are widely used in critical care settings [27]. Among them, CytoSorb ® , a CE-approved hemoadsorber, can significantly remove cytokines, bilirubin, toxic bile acids, and myoglobin in the circulating blood [28][29][30][31]. Equipped with highly porous, biocompatible sorbent polystyrene divinylbenzene beads, CytoSorb ® cartridges have a total surface area of >45,000 m 2 and are capable of adsorbing various hydrophobic cytokine molecules with a molecular weight ranging from 5 to 55 kDa [22].…”
Section: Rationale For Hemoadsorption Therapy In Ie Patients Undergoi...mentioning
confidence: 99%
“…Currently, CytoSorb ® (CytoSorbents Europe GmbH, Berlin, Germany), HA 330 (Jafron Biomedical Co., Ltd., Zhuhai, China), and Toraymyxin™ (Toray Medical Co., Ltd., Tokyo, Japan) are three mainstream hemoadsorbers that are widely used in critical care settings [27]. Among them, CytoSorb ® , a CE-approved hemoadsorber, can significantly remove cytokines, bilirubin, toxic bile acids, and myoglobin in the circulating blood [28][29][30][31]. Equipped with highly porous, biocompatible sorbent polystyrene divinylbenzene beads, CytoSorb ® cartridges have a total surface area of >45,000 m 2 and are capable of adsorbing various hydrophobic cytokine molecules with a molecular weight ranging from 5 to 55 kDa [22].…”
Section: Rationale For Hemoadsorption Therapy In Ie Patients Undergoi...mentioning
confidence: 99%
“…We have carefully reviewed the recent study by Gräfe et al [1], titled "Correlation between Bilirubin Elimination with the Cytokine Adsorber CytoSorb ® and Mortality in Critically Ill Patients with Hyperbilirubinemia," published in Blood Purification on October 11, 2023. We would like to express some concerns and seek clarification on certain aspects of the study.…”
Section: Dear Editormentioning
confidence: 99%
“…This finding contradicts previous studies, which [6] reported significant bilirubin, AST and vasopressor reduction by hemadsorption. As Gräfe et al [1] did not quantify bilirubin removal by hemadsorption, it becomes challenging to assess the effectiveness of this particular blood purification technique in the described scenario. Moreover, the quantitative impact of all the extracorporeal therapies, including CytoSorb, on bilirubin levels may not be assessed by means of systemic measurements alone.…”
Section: Dear Editormentioning
confidence: 99%
“…Currently, CytoSorb® (CytoSorbents Europe GmbH, Berlin, Germany), HA 330 (Jafron Biomedical Co., Ltd, Zhuhai, China) and Toraymyxin™ (Toray Medical Co., Ltd, Tokyo, Japan) are three mainstream hemoadsorbers that are widely used in critical care settings [27]. Among them, CytoSorb®, a CE-approved hemoadsorber, can significantly remove cytokines, bilirubin, toxic bile acids, and myoglobin in the circulating blood [28][29][30][31]. Equipped with highly porous, biocompatible sorbent polystyrene divinylbenzene beads, CytoSorb® cartridges have a total surface area of > 45,000 m 2 and are capable of adsorbing various hydrophobic cytokine molecules within the 5-55 kDa molecular weight range [22].…”
Section: Rationale For Hemoadsorption Therapy In Ie Patients Receivin...mentioning
confidence: 99%